Review article: Outcomes of patients who are not transported following ambulance attendance: A systematic review and meta‐analysis. (3rd April 2019) - Yeung, Timothy; Shannon, Brendan; Perillo, Samuel; Nehme, Ziad; Jennings, Paul; Olaussen, Alexander
Abstract: The aim of this systematic review and meta‐analysis was to evaluate the outcomes of patients who are not transported to hospital following ambulance attendance. A database search was conducted using PubMed, Medline, Embase, CINAHL and Cochrane Library. Studies were included if they analysed the outcomes of patients who were not transported following ambulance attendance. The primary outcome of this review was subsequent presentation to an ED following a non‐transport decision. Secondary outcome measures included hospital admission, subsequent presentation to alternative service provider (e.g. private physician), and death at follow up. The search yielded 1953 non‐duplicate articles, of which 10 met the inclusion criteria. Three studies specified that the non‐transport decision was emergency medical services (EMS)‐initiated, seven studies did not specify. Meta‐analysis found substantial heterogeneity between estimates ( I 2 >50%) that was likely because of differences in study design, length of follow up, patient demographic and sample size. Between 5% and 46% (pooled estimate 21%; 95% CI 11–31%) of non‐transport patients subsequently presented to ED. Few (pooled estimate 8%; 95% CI 5–12%) EMS‐initiated non‐transport patients were admitted to hospital compared to the unspecified group (pooled estimate 40%; 95% CI 7–72%). Mortality rates were low across included studies. Studies found varying estimates for the proportion of patients discharged at the scene that subsequently presented to ED. Few patients were admitted to hospital when the non‐transport decision was initiated by EMS, indicating EMS triage is a relatively safe practice. More research is needed to elucidate the context of non‐transport decisions and improve access to alternative pathways.